Multidrug Resistant Acinetobacter baumannii Biofilms: Evaluation of Phenotypic–Genotypic Association and Susceptibility to Cinnamic and Gallic Acids - Sherif, Mahmoud M.; Elkhatib, Walid F.; Khalaf, Wafaa S.; Elleboudy, Nooran S.; Abdelaziz, Neveen A. (Frontiers in Microbiology, 2021)
Acinetobacter baumannii (A. baumannii) armed with multi-drug resistance (MDR) and biofilm-forming ability is increasingly recognized as an alarming pathogen. A deeper comprehension of the correlation between these two armouries is required in circumventing its infections. This study examined the biofilm-forming ability of the isolates by crystal violet staining and the antibiotic susceptibility by broth microdilution method. The genetic basis of the MDR and biofilm-forming phenotypes was screened by polymerase chain reaction. The antimicrobial activities of cinnamic and gallic acids against planktonic cells and biofilms of A. baumannii were investigated and the findings were confirmed with scanning electron microscopy (SEM). Among 90 A. baumannii isolates, 69 (76.6%) were MDR and all were biofilm formers, they were classified into weak (12.2%), moderate (53.3%) and strong (34.5%) biofilm formers. Our results underlined a significant association between MDR and enhanced biofilm formation. Genotypically, presence of blaVIM, and blaOXA-23 genes along with biofilm-related genes (ompA, bap and csuE) was statistically associated with the biofilm- forming abilities. Impressively, both gallic and cinnamic acids could significantly reduce the MDR A. baumannii biofilms with variable degrees dependent on the phenotype-genotype characteristics of the tested isolates. The current findings may possess future therapeutic impact through augmenting antimicrobial arsenal against life-threatening infections with MDR A. baumannii biofilms.